Um olhar pedagógico sobre o cuidar do humano no contexto Umbandista - Silva, Francisco Ferreira da (2009)
This dissertation has as objective to analyze umbanda focusing on the manner by which the priests and the priestesses, who were interviewed, started to follow this religion, as well as, this work aims to study the pedagogic process applied in the new followers' preparation. Another subject studied was how the different backyards establish a relationship with each other and with the federations. Based on a qualitative methodology, I approached the knowledge and symbols that compose the universe of umbanda. The temples which were studied are located in the periphery of João Pessoa city and their spiritual leaders raised, through the religion, a social status at their community that, they would not probably have, in the case of not having the support of the religion. The saint's fathers and saint's mothers who were interviewed were not born umbandistas, but they moved from a certain religious credo to the universe of umbanda. It is important to point out that this religious traffic occurred because of pain, in other words, the entrance of the new cult in their lives occurred by reasons of disease. From the interviewees' speech, it can be observed that it is a religion that is built in the daily contact with the guides and masters. The knowledge and the new experiences are not looked for in the books, but in the constant practice of the charity. In relation to new followers' preparation, the use of the oral tradition is observed, by means of which the beginner will learn how to decode the symbolic universe when dialoguing with the oldest. Regarding the interactions among the backyards, a great disunion is observed, what represents a difficulty to the political organization of umbanda in relation to a flag and the own religion. This divergence also appears because of the different federations that have appeared along the time. Differently from Rio de Janeiro and São Paulo, two of the first Brazilian centers of umbanda, the first federation of Paraíba just appeared during the 1960 s under the protection of the law of liberation of the Afro-Brazilian cults in the state.